The Impact of Age upon Contingency Planning for Multiple-casualty Incidents Based on a Single Center's Experience. Issue 5 (17th August 2016) - Ashkenazi, Itamar; Einav, Sharon; Olsha, Oded; Turegano-Fuentes, Fernando; Krausz, Michael M.; Alfici, Ricardo
Abstract: Introduction: Trauma patients in the extremes of age may require a specialized approach during a multiple-casualty incident (MCI). Problem: The aim of this study was to examine the type of injuries encountered in children and elderly patients and the implications of these injuries for treatment and organization. Methods: A review of medical record files of patients admitted in MCIs in one Level II trauma center was conducted. Patients were classified according to age: children (≤12 years), adults (between 12-65 years), and elders (≥65 years). Results: The files of 534 were screened: 31 (5.8%) children and 54 (10.1%) elderly patients. One-third of the elderly patients were either moderately or severely injured, compared to only 6.5% of the children and 11.1% of the adults (P<.001). Elderly patients required more blood transfusions (P=.0001), more computed tomography imaging (P=.0001), and underwent more surgery (P=.0004). Elders were hospitalized longer (P=.0003). There was no mortality among injured children, compared to nine (2.0%) of the adults and seven (13.0%) of the elderly patients (P<.0001). All the adult deaths occurred early and directly related to their injuries, whereas most of the deaths among the elderly patients (four out of seven) occurred late and were due to complications and multiple organ failure. Conclusions: Injury at an older age confers an increased risk of complications and death in victims of MCIs. I Ashkenazi, S Einav, O Olsha, F Turegano-Fuentes, MM Krausz, R Alfici .The impact of age upon contingency planning for multiple-casualty incidents based on a single center's experience .Prehosp Disaster Med .2016 ;31 (5 ):492 –497 .